(3efThQ Edi LeGYI CHj fRhGH TjhN GdehVhYs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3hUd cJGHc jG CNj GdYRjR Ydi hYfOi CWGd Gddg HbGc hCOGe YRc hfYec hhbaJ Ydjg hTcQJ ef dGjNjH TcQg s
(3BNQgG (B:s
(3adjHdZ Pdc hjaQb eG jMUd efg Ydi GdVYaGA ef GdCgd hGdHfGJ hCeG GdSja GdPi YfO CNj CHj GdNjQ agh CMb Hg Ydi LejY GdMGdGJ hGdSdGe dBd YHO Gddg hBd SdjeGf JeJ Hefg hdi GdCeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B98s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis